2020
DOI: 10.1002/pbc.28271
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term renal function after treatment for unilateral, nonsyndromic Wilms tumor. A report from the St. Jude Lifetime Cohort Study

Abstract: Background The impact of specific treatment modalities on long‐term renal function and blood pressure among adult survivors of Wilms tumor (WT) has not been well documented. Methods Among 40 WT survivors and 35 noncancer controls, we estimated the glomerular filtration rate (eGFR) using the Chronic Kidney Disease‐Epidemiology (CKD‐EPI) equations with and without cystatin C, obtained 24‐hour ambulatory blood pressure readings, and, among survivors only, measured 99mTc diethylenetriamine pentaacetic acid (DTPA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…In one study, patients exposed to radiotherapy but not to cardiotoxic chemotherapy had decreased left ventricle wall thickness and wall mass similar to those who received anthracyclines [ 25 ]. This mechanism was confirmed by a report that demonstrates the strong association between abdomen and liver radiation (>15 Gy) and portal hypertension in CCS of Wilms Tumor [ 26 ]. Patients exposed to abdomen radiation have the highest risk of developing type 2 diabetes and insulin intolerance as a result of adipose damage after radiation, which causes cytokine release and chronic low-grade inflammation.…”
Section: Pathogenesis Of Metabolic Syndrome and Cardiovascular Diseas...supporting
confidence: 66%
“…In one study, patients exposed to radiotherapy but not to cardiotoxic chemotherapy had decreased left ventricle wall thickness and wall mass similar to those who received anthracyclines [ 25 ]. This mechanism was confirmed by a report that demonstrates the strong association between abdomen and liver radiation (>15 Gy) and portal hypertension in CCS of Wilms Tumor [ 26 ]. Patients exposed to abdomen radiation have the highest risk of developing type 2 diabetes and insulin intolerance as a result of adipose damage after radiation, which causes cytokine release and chronic low-grade inflammation.…”
Section: Pathogenesis Of Metabolic Syndrome and Cardiovascular Diseas...supporting
confidence: 66%
“…Another study examined long-term renal function after unilateral RN in nonsyndromic patients. 18 At 28 years of follow-up, GFR was similar to that of controls, except for those who received RT, and no patients developed ESRD. There was, however, a significant increased risk for hypertension in those with WT.…”
Section: Long-term Concerns For Rnmentioning
confidence: 69%
“…It better reflects actual BP, and nocturnal BP is the most significant predictor of CVD [19e21]. Studies in various cohorts of CCS using ABPM [15,22e26] reported insufficient nocturnal dipping [23,24,26] or deviant night-time diastolic BP (DBP) [15,22,25]. Unfortunately, these studies included small patient numbers.…”
Section: Introductionmentioning
confidence: 99%